Method for increasing proportion of intragranular acicular ferrite in structure and product
By adding oxide metallurgy elements to the offshore steel liquid and applying electrical pulse treatment at different stages, the problem of difficulty in increasing the proportion of in-crystal needle-shaped ferrite in the offshore steel plate in the prior art is solved, and the effect of improving welding performance is achieved.
Patent Information
- Application Number
- CN202411791352.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to increase the proportion of needle-shaped ferrite in crystals in offshore steel plates through physical means, thereby limiting the weldability of large-line energy welding.
By adding oxide metallurgy elements to the liquid steel and performing electrical pulse processing in the liquid steel stage and solidification stage, the proportion of needle-shaped ferrite in the crystal is increased by using the disturbance and free energy introduced by the electric pulse.
The proportion of needle-shaped ferrite in crystal in marine steel structure has been significantly improved, and the impact performance and welding performance of marine steel plates have been improved.
Smart Images

Figure HDA0005175388750000011
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metallurgy, and in particular relates to a method and a product for increasing the proportion of intracrystalline acicular ferrite in a structure. Background Art
[0002] Large-scale marine engineering equipment is an important support for marine strategy and is widely used in offshore wind power, oil and gas engineering, shipbuilding, island and reef construction and other fields. Due to long-term exposure to harsh environments of wind, waves, currents and erosion, the comprehensive performance of steel plates, especially weldability, is increasingly demanding, which seriously restricts the development of marine resources and the implementation of energy strategies.
[0003] At present, most of the medium and extra-thick offshore steel plates are prepared by oxide metallurgy and connected by high-energy line welding technology. Oxide metallurgy technology uses inclusions in molten steel to induce the formation of acicular ferrite, thereby improving the weldability of the steel plate. However, current research is mainly on the molten steel conditions and smelting conditions that induce the nucleation of acicular ferrite. There is still a lack of research on how to increase the proportion of acicular ferrite in the organization through physical means. Therefore, there is an urgent need for an efficient, green and convenient means to increase the proportion of intracrystalline acicular ferrite in the organization to improve the high-energy line weldability of offshore steel plates.
[0004] In addition, the prior art 1 (CN118441122A) discloses a device and method for removing inclusions in molten steel by using pulse current and bubbles. Although a pulse current is applied, the purpose is to drive the inclusions to move in a directional manner along the current density gradient, and the nucleation of acicular ferrite in the structure is not studied.
[0005] Prior art 2 (CN117862439A) discloses a device and method for suppressing the growth of inclusions in a continuous casting mold by using a pulse current, but its main purpose is to suppress the growth of inclusions, and the influence of the pulse current on the steel structure is not studied.
[0006] Prior art 3 (CN115921828A) discloses a method for achieving uniform distribution of inclusions in the solidified structure of molten steel, but it only applies pulse current during the solidification process of the molten steel, and does not study the effect of the pulse current on the treatment of the molten steel in the melt stage. Currently, none of these technologies have studied the effect of pulse current on the molten steel, the nucleation of acicular ferrite in the structure, and the steel structure. Summary of the invention
[0007] In order to overcome the problems existing in the prior art, the present invention provides a method and product for increasing the proportion of intracrystalline acicular ferrite in a structure.
[0008] A method for increasing the proportion of intracrystalline acicular ferrite in a structure, comprising: cleaning a raw material, heating and melting it, and adding oxide metallurgy to obtain a molten steel to be treated; inserting an electrode into the molten steel to be treated and performing an electric pulse treatment for a first time period, performing an electric pulse treatment for a second time period during the solidification stage of the molten steel to be treated until it is completely solidified, and obtaining an ingot sample, wherein the first time period is different from the second time period, and the pulse treatment in the first time period and the pulse treatment in the second time period are used to increase the proportion of intracrystalline acicular ferrite in the structure of marine engineering steel.
[0009] According to the aspects and any possible implementations described above, an implementation is further provided, wherein the process parameters of the electric pulse are a pulse frequency of 10 Hz-10000 Hz, a current of 10 A-1000 A, a pulse width of 1 μs-500 ms and a voltage of 1-36 V.
[0010] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the method includes the following:
[0011] S1. Cut the raw material into cubic samples by wire cutting, and use sandpaper to polish, clean and dry the surface of the three-dimensional sample;
[0012] S2. Selecting the electrode material, electrode size, electric pulse power supply and electric pulse wire according to the size of the three-dimensional sample;
[0013] S3. The three-dimensional sample raw material is placed in an atmosphere furnace and heated to melt and oxide metallurgy is added. After a period of heat preservation, the molten steel to be treated is obtained;
[0014] S4. The electrode is inserted into the molten steel to be treated, the two electrodes are placed on both sides of the crucible, and the electrode is inserted into the bottom of the crucible, and the electric pulse treatment is started. After the first time period of the molten steel stage, the electric pulse treatment is performed in the second time period during the solidification stage of the molten steel;
[0015] S5. After the second time period ends, the electric pulse treatment is stopped until the molten steel is completely solidified to obtain an ingot.
[0016] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the first time period is 1 min-20 min, and the second time period is 30 min-60 min.
[0017] According to the aspects described above and any possible implementation method, an implementation method is further provided, wherein the material of the electrode is high-purity iron or tungsten, the diameter of the electrode is 8-12 mm, the length is 670 mm, the wire is nickel-plated copper wire, and the electric pulse power supply includes positive and negative electrodes.
[0018] According to the above aspects and any possible implementation, an implementation is further provided, wherein the oxide metallurgy is one or more of Mg, Ti, Zr and rare earth elements.
[0019] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the method further includes:
[0020] S6. The ingot was cut into a 10 mm × 10 mm × 50 mm cuboid, and the impact performance was measured at an impact temperature of -20 ° C to obtain an impact test sample;
[0021] S7. Cut the impact test sample into a cubic sample of 10 mm × 10 mm × 10 mm, corrode the sample, and observe and count the area ratio of intracrystalline acicular ferrite in the sample.
[0022] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the atmosphere of the atmosphere furnace is argon.
[0023] According to the above aspects and any possible implementation, an implementation is further provided, wherein the period of time is 30 minutes.
[0024] The present invention also provides a marine engineering steel or a steel for high-energy-input welding, wherein the marine engineering steel or the steel for high-energy-input welding is prepared by the method described, wherein the proportion of intracrystalline acicular ferrite in the structure is increased by 25-75%.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The method of increasing the proportion of intracrystalline acicular ferrite in the structure of the present invention comprises: cleaning the raw materials, heating and melting them, and adding oxide metallurgy to obtain a molten steel to be treated; inserting an electrode into the molten steel to be treated for an electric pulse treatment in a first time period, and performing an electric pulse treatment in a second time period during the solidification stage of the molten steel to be treated until it is completely solidified, and obtaining an ingot sample, wherein the first time period is different from the second time period, and the pulse treatment in the first time period and the pulse treatment in the second time period are used to increase the proportion of intracrystalline acicular ferrite in the structure of offshore steel. The present invention improves the impact performance of offshore steel plates by increasing the proportion of intracrystalline acicular ferrite in the structure of offshore steel or steel for high-line energy welding under the combined action of the disturbance caused by the electric pulse and the free energy introduced by the current, and ultimately improves the welding performance of the offshore steel plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The figures are the treatment effect diagrams of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0028] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific implementation methods described below, and similar technologies and methods should be considered to be within the scope of protection of the present invention. In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.
[0029] It should be clear that the embodiments described in the present invention are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0031] The present invention provides a method for increasing the proportion of intracrystalline acicular ferrite in a structure, which is used for marine engineering steel or steel for high-energy wire welding, comprising: cleaning the raw materials, heating and melting them, and adding oxide metallurgy to obtain a molten steel to be treated; inserting an electrode into the molten steel to be treated and performing an electric pulse treatment for a first time period, performing an electric pulse treatment for a second time period during the solidification stage of the molten steel to be treated until it is completely solidified, and obtaining an ingot sample, wherein the first time period is different from the second time period, and the pulse treatment in the first time period and the pulse treatment in the second time period are used to increase the proportion of intracrystalline acicular ferrite in the marine engineering steel structure (please verify whether it is appropriate), that is, the method is implemented by applying electric pulses in the molten steel and solidification stages, and in the existing means, no other treatment is performed after the oxide metallurgy, and the present invention performs oxide metallurgy in the molten steel stage, and then applies pulse current in the molten steel stage and the solidification stage, so as to increase the proportion of intracrystalline acicular ferrite by the free energy introduced by the pulse current.
[0032] Preferably, the process parameters of the electric pulses used in the two time periods are pulse frequency 10Hz-10000Hz, current size 10A-1000A, pulse width 1μs-500ms, and voltage 1-36V. 10Hz-10000Hz can fully reflect the effect of electric pulses in low and high frequency conditions; 10A-1000A can reflect the effect of electric pulses in low and high current density conditions; pulse width can change the action time of electric pulses in one cycle; 1-36V is a safe voltage for the human body.
[0033] Specifically, the process parameters of the electric pulse can be selected as follows: the electric pulse frequency is 200Hz, the current is 1000A, the voltage is 36V, and the pulse width is 200μm; the electric pulse frequency is 10000Hz, the current is 1000A, the voltage is 36V, and the pulse width is 200μm; the electric pulse frequency is 1000Hz, the current is 1000A, the voltage is 36V, and the pulse width is 200μm; the electric pulse frequency is 200Hz, the current is 200A, the voltage is 36V, and the pulse width is 200μm; the electric pulse frequency is 200Hz, the current is 20A, the voltage is 36V, and the pulse width is 200μm, or the electric pulse frequency is 200Hz, the current is 10000A, the voltage is 36V, and the pulse width is 200μm, which can be selected according to the quality of the raw materials used.
[0034] Preferably, the metal steel liquid carrying container is an alumina or magnesium oxide crucible, and the working temperature of the alumina crucible or the magnesium oxide crucible is above the melting point of marine steel, which can ensure that the sample is completely melted and prevent the steel liquid from leaking out; the electrode is a pure iron electrode or a tungsten electrode, and the pure iron electrode or the tungsten electrode is used to ensure that the electrode does not affect the steel liquid or that the steel liquid does not melt; the metal wire is a nickel-plated copper wire, and the nickel-plated copper wire is used because of its good conductivity and high temperature resistance.
[0035] Preferably, the first time period is the melting stage, which is 1-20 minutes, and the second time period is the solidification stage, which is 30 minutes to 60 minutes.
[0036] Preferably, the method comprises the following steps:
[0037] S1. Raw material processing
[0038] Cut the offshore steel raw materials or steel raw materials for high-energy line welding into cubic samples by wire cutting, polish the sample surface with sandpaper to make it smooth, clean the sample surface with ultrasound, and dry it in a drying oven to prevent rust or stains on the sample surface from affecting the melting.
[0039] S2. Pulse current processing structure setting
[0040] The electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected according to the sample size in step S1. The larger the sample mass, the larger the required electrode size, the greater the power required by the pulse power supply, and the larger the cross-section of the wire.
[0041] S3. Oxide metallurgical treatment
[0042] The raw materials in step S1 are placed in an atmosphere furnace, heated and melted, and oxide metallurgical elements are added to obtain molten steel to be treated. The addition of oxide metallurgical elements for treatment can obtain high melting point inclusions as needle-shaped ferrite nucleation particles.
[0043] S4, pulse current processing
[0044] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start electric pulse treatment, and promote the uniform distribution of oxide metallurgical elements in the molten steel; after a period of treatment in the molten steel stage, the electric pulse treatment is performed again when the molten steel enters the solidification stage, and the free energy introduced by the electric pulse reduces the energy required for the formation of acicular ferrite, thereby promoting the formation of acicular ferrite.
[0045] S5. The molten steel solidifies to obtain an ingot
[0046] After the molten steel in step S4 is subjected to electric pulse treatment for a period of time during the solidification stage, the electric pulse treatment is stopped and the sample is cooled to room temperature with the furnace, which can ensure the quality of the ingot and reduce the formation of pores until the molten steel is completely solidified to obtain an ingot steel sample.
[0047] S6. Sample impact performance test
[0048] The ingot steel sample in step S5 is taken out, and a 10mm×10mm×50mm rectangular sample is obtained by electric spark wire cutting. The impact performance of the sample is measured by an impact testing machine. The impact temperature is -20°C. The impact energy of the material is closely related to the proportion of acicular ferrite in the structure. As the proportion increases, the impact energy increases accordingly. This step can measure the specific impact energy and intuitively see the effect of the electric pulse.
[0049] S7. Detection of intracrystalline acicular ferrite in sample organization
[0050] The impact test sample in S6 was cut again to obtain a 10mm×10mm×10mm three-dimensional sample. After the sample was corroded by nitric acid alcohol, it was observed under a light microscope. The area ratio of intracrystalline acicular ferrite in the sample was obtained by statistical analysis using ImageJ software. The statistical results showed that the electric pulse was applied to the molten steel and the molten steel solidification stage in step S4. When the electric pulse parameters were 200Hz, 1000A, 36V, and the action time of the molten steel stage was 10min, the proportion of intracrystalline acicular ferrite increased by 73.9% compared with the traditional technology; when the electric pulse parameters were 10000Hz, 1000A, 36V, and the action time of the molten steel stage was 10min, the proportion of intracrystalline acicular ferrite increased by 26% compared with the traditional technology; when the electric pulse parameters were 1000Hz, 1000A, 36V, and the action time of the molten steel stage was 10min, the proportion of intracrystalline acicular ferrite increased by 26% compared with the traditional technology. When A, 36V, and the action time of the molten steel stage is 10min, the proportion of needle-shaped ferrite in the crystal is increased by 53% compared with the traditional technology; when the electric pulse parameters are 200Hz, 200A, 36V, and the action time of the molten steel stage is 10min, the proportion of needle-shaped ferrite in the crystal is increased by 47% compared with the traditional technology; when the electric pulse parameters are 200Hz, 20A, 36V, and the action time of the molten steel stage is 10min, the proportion of needle-shaped ferrite in the crystal is increased by 26% compared with the traditional technology; when the electric pulse parameters are 200Hz, 1000A, 36V, and the action time of the molten steel stage is 5min, the proportion of needle-shaped ferrite in the crystal is increased by 48% compared with the traditional technology. In summary, the present invention increases the proportion of needle-shaped ferrite in the crystal compared with the traditional technology, and the proportion of needle-shaped ferrite in the crystal is increased by 25%-75%.
[0051] Preferably, the mass of the marine steel sample in step S1 is 200g-2000g. When the mass exceeds 2000g, the required pulse power needs to be increased, and the current size will also be further increased.
[0052] Preferably, the electrode material in step S2 is a high-purity iron rod or a tungsten rod, the electrode diameter is 8-12 mm, the length is 670 mm, and the wire is a nickel-plated copper wire.
[0053] Preferably, in step S3, the atmosphere of the atmosphere furnace is argon, and the micro-alloying elements are added to the molten steel through a corundum tube to perform oxide metallurgy.
[0054] Preferably, the oxide metallurgical element in step S3 may be one or more of Mg, Ti, Zr and rare earth elements.
[0055] Preferably, the steel sample prepared by the method shows that the impact energy is increased by 20%-80% when subjected to an impact performance test.
[0056] Pulse current is an efficient and energy-saving treatment method that can regulate the structure of steel. The present invention applies electric pulses after adding oxide metallurgy to the molten steel, thereby greatly increasing the proportion of intracrystalline acicular ferrite in the steel structure, reducing the steps of regulating the elemental composition of the molten steel in the conventional steelmaking process, and achieving fast and green regulation. The treatment time of the electric pulse used in the present invention is 1min to 20min in the melt stage and 30min to 60min in the solidification stage. This method can significantly increase the proportion of acicular ferrite in the steel structure. At the same time, the present invention significantly increases the proportion of acicular ferrite in the ingot structure by controlling the electric pulse parameters, and ultimately improves the welding performance of marine steel.
[0057] As an embodiment disclosed in the present invention, the present invention also provides a marine engineering steel or steel for high-line energy welding, which is prepared by the method. The proportion of acicular ferrite in the structure of the marine engineering steel or steel for high-line energy welding obtained by the method is increased by 25-75% compared with traditional oxide metallurgy technology.
[0058] Comparative Examples and Examples are used below to illustrate:
[0059] Comparative Example 1
[0060] This comparative example is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0061] S1. Raw material processing
[0062] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180 mesh sandpaper, the sample surface was cleaned by ultrasound, and placed in a drying oven to dry for 2 h.
[0063] S2. Pulse current processing structure setting
[0064] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0065] S3. Oxide metallurgical treatment
[0066] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added, oxide metallurgy is performed, and the heat preservation time is 30 min to obtain molten steel to be treated;
[0067] S4, pulse current processing
[0068] Inserting the electrodes in step S2 into the molten steel in step S3, placing the two electrodes on both sides of the crucible, and inserting the electrodes into the bottom of the crucible without performing electric pulse treatment;
[0069] S5. The molten steel solidifies to obtain an ingot
[0070] After the molten steel in step S4 enters the solidification stage for 30 minutes, the molten steel is cooled along with the furnace until it is completely solidified to obtain an ingot;
[0071] S6. Sample impact performance test
[0072] The steel sample in step S5 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0073] S7. Detection of intracrystalline acicular ferrite in sample organization
[0074] The impact test samples in S6 were cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, they were observed under a light microscope, and the area percentage of intracrystalline acicular ferrite in the samples was obtained by statistics using ImageJ software.
[0075] In this comparative example 1, only Ti element is added for oxide metallurgy without applying electric pulse treatment. The impact energy of the steel is measured to be 78 J, and the area of intragranular acicular ferrite in the structure accounts for 46%.
[0076] Comparative Example 2
[0077] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0078] S1. Raw material processing
[0079] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180 mesh sandpaper, the sample surface was cleaned by ultrasound, and placed in a drying oven to dry for 2 h.
[0080] S2. Pulse current processing structure setting
[0081] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0082] S3. Oxide metallurgical treatment
[0083] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti and 0.02 wt.% Ni-Mg alloy are added, oxide metallurgy is performed, and the heat preservation time is 30 min to obtain molten steel to be treated;
[0084] S4, pulse current processing
[0085] Inserting the electrodes in step S2 into the molten steel in step S3, placing the two electrodes on both sides of the crucible, and inserting the electrodes into the bottom of the crucible without performing electric pulse treatment;
[0086] S5. The molten steel solidifies to obtain an ingot
[0087] After the molten steel in step S4 enters the solidification stage for 30 minutes, the molten steel is cooled along with the furnace until it is completely solidified to obtain an ingot;
[0088] S6. Sample impact performance test
[0089] The sample in step S5 is taken out, and a cuboid of 10 mm×10 mm×50 mm is obtained by wire electric discharge cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0090] S7. Detection of intracrystalline acicular ferrite in sample organization
[0091] The impact test samples in S6 were cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, they were observed using a light microscope, and the area fraction of intracrystalline acicular ferrite in the samples was obtained using ImageJ software.
[0092] In this comparative example 2, Ti and Mg were added to perform oxide metallurgy without applying electric pulse treatment. The impact energy of the steel was measured to be 85 J, and the area of intragranular acicular ferrite in the structure accounted for 51%.
[0093] Example 1
[0094] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0095] S1. Raw material processing
[0096] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180-mesh sandpaper, the sample surface was cleaned by ultrasound, and the sample was placed in a drying oven for 2 h.
[0097] S2. Pulse current processing structure setting
[0098] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0099] S3. Oxide metallurgical treatment
[0100] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added for oxide metallurgy, and the heat preservation time is 30 min to obtain a molten steel to be treated;
[0101] S4, pulse current processing
[0102] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start the electric pulse treatment, and after the molten steel stage is treated for 10 minutes, perform the electric pulse treatment on the solidification stage of the molten steel; wherein the electric pulse frequency is 200 Hz, the current size is 1000 A, the voltage is 36 V, and the pulse width is 200 μm;
[0103] S5. Sample impact performance test
[0104] The steel sample in step S4 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0105] S6. Detection of intracrystalline acicular ferrite in sample organization
[0106] The impact test sample in S5 was cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, it was observed under a light microscope, and the area percentage of intracrystalline acicular ferrite in the sample was obtained by statistics using ImageJ software.
[0107] like Figure 1 As shown, the results show that relative to Comparative Examples 1 and 2, the impact energy increased from 78J to 141J, an increase of 80.76%; the area ratio of intracrystalline acicular ferrite increased from 45% (Comparative Example 1) to 83%, an increase of 73.9%; and increased from 51% (Comparative Example 2) to 83%.
[0108] Example 2
[0109] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0110] S1. Raw material processing
[0111] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180 mesh sandpaper, the sample surface was cleaned by ultrasound, and placed in a drying oven to dry for 2 h.
[0112] S2. Pulse current processing structure setting
[0113] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0114] S3. Oxide metallurgical treatment
[0115] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added for oxide metallurgy, and the heat preservation time is 30 min to obtain a molten steel to be treated;
[0116] S4, pulse current processing
[0117] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start the electric pulse treatment, and after the molten steel stage is treated for 10 minutes, perform the electric pulse treatment on the solidification stage of the molten steel; wherein the electric pulse frequency is 10000 Hz, the current size is 1000A, the voltage is 36V, and the pulse width is 200μm;
[0118] S5. Sample impact performance test
[0119] The steel sample in step S4 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0120] S6. Detection of intracrystalline acicular ferrite in sample organization
[0121] The impact test sample in S5 was cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, it was observed under a light microscope, and the area percentage of intracrystalline acicular ferrite in the sample was obtained by statistics using ImageJ software.
[0122] The results show that compared with comparative example 1, the impact energy increases from 78 J to 101 J, an increase of 33%; the area ratio of intracrystalline acicular ferrite increases from 46% to 58%, an increase of 26%.
[0123] Example 3
[0124] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0125] S1. Raw material processing
[0126] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180-mesh sandpaper, the sample surface was cleaned by ultrasound, and the sample was placed in a drying oven for 2 h.
[0127] S2. Pulse current processing structure setting
[0128] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0129] S3. Oxide metallurgical treatment
[0130] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added for oxide metallurgy, and the heat preservation time is 30 min to obtain a molten steel to be treated;
[0131] S4, pulse current processing
[0132] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start the electric pulse treatment, and after the molten steel stage is treated for 10 minutes, perform the electric pulse treatment on the solidification stage of the molten steel; wherein the electric pulse frequency is 1000 Hz, the current size is 1000 A, the voltage is 36 V, and the pulse width is 200 μm;
[0133] S5. Sample impact performance test
[0134] The steel sample in step S4 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0135] S6. Detection of intracrystalline acicular ferrite in sample organization
[0136] The impact test sample in S5 was cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, it was observed under a light microscope, and the area percentage of intracrystalline acicular ferrite in the sample was obtained by statistics using ImageJ software.
[0137] The results show that compared with comparative example 1, the impact energy increases from 78 J to 121 J, an increase of 55%; the area ratio of intracrystalline acicular ferrite increases from 45% to 69%, an increase of 53%.
[0138] Example 4
[0139] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0140] S1. Raw material processing
[0141] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180-mesh sandpaper, the sample surface was cleaned by ultrasound, and the sample was placed in a drying oven for 2 h.
[0142] S2. Pulse current processing structure setting
[0143] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0144] S3. Oxide metallurgical treatment
[0145] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added for oxide metallurgy, and the heat preservation time is 30 min to obtain a molten steel to be treated;
[0146] S4, pulse current processing
[0147] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start the electric pulse treatment, and after the molten steel stage is treated for 10 minutes, perform the electric pulse treatment on the solidification stage of the molten steel; wherein the electric pulse frequency is 200 Hz, the current size is 200 A, the voltage is 36 V, and the pulse width is 200 μm;
[0148] S5. Sample impact performance test
[0149] The steel sample in step S4 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0150] S6. Detection of intracrystalline acicular ferrite in sample organization
[0151] The impact test sample in S6 was cut into 10 mm × 10 mm × 10 mm, and after being corroded by nitric acid alcohol, the area ratio of intragranular acicular ferrite in the sample structure was obtained;
[0152] The results show that compared with comparative example 1, the impact energy increases from 78 J to 119 J, an increase of 53%; the area ratio of intracrystalline acicular ferrite increases from 46% to 67%, an increase of 47%.
[0153] Example 5
[0154] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0155] S1. Raw material processing
[0156] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180 mesh sandpaper, the sample surface was cleaned by ultrasound, and placed in a drying oven to dry for 2 h.
[0157] S2. Pulse current processing structure setting
[0158] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0159] S3. Oxide metallurgical treatment
[0160] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added for oxide metallurgy, and the heat preservation time is 30 min to obtain a molten steel to be treated;
[0161] S4, pulse current processing
[0162] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start the electric pulse treatment, and after the molten steel stage is treated for 10 minutes, perform the electric pulse treatment on the solidification stage of the molten steel; wherein the electric pulse frequency is 200 Hz, the current size is 20 A, the voltage is 36 V, and the pulse width is 200 μm;
[0163] S5. Sample impact performance test
[0164] The steel sample in step S4 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0165] S6. Detection of intracrystalline acicular ferrite in sample organization
[0166] The impact test sample in S5 was cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, it was observed under a light microscope, and the area percentage of intracrystalline acicular ferrite in the sample was obtained by statistics using ImageJ software.
[0167] The results show that compared with comparative example 1, the impact energy increases from 78 J to 104 J, an increase of 33%; the area ratio of intracrystalline acicular ferrite increases from 46% to 58%, an increase of 26%.
[0168] Example 6
[0169] This embodiment is a novel oxide metallurgy technology under an electric pulse external field, and the method comprises the following steps:
[0170] S1. Raw material processing
[0171] The raw material was cut into 1 kg cubic samples by wire cutting, the sample surface was polished smooth with 180-mesh sandpaper, the sample surface was cleaned by ultrasound, and the sample was placed in a drying oven for 2 h.
[0172] S2. Pulse current processing structure setting
[0173] According to the sample size in step S1, the electrode material, electrode size, electric pulse power supply, and electric pulse wire are selected; the electrode is a pure iron electrode with a size of φ12mm×670mm; the electrode rod is connected to the positive and negative electrodes of the power supply respectively, and the connecting wire is a nickel-plated copper wire;
[0174] S3. Oxide metallurgical treatment
[0175] 1 kg of the raw material in step S1 is placed in a corundum crucible of φ80 mm×100 mm, heated and melted in an atmosphere furnace at a melting temperature of 1570° C., 0.02 wt.% Ti is added for oxide metallurgy, and the heat preservation time is 30 min to obtain a molten steel to be treated;
[0176] S4, pulse current processing
[0177] Insert the electrodes in step S2 into the molten steel in S3, place the two electrodes on both sides of the crucible, and insert the electrodes into the bottom of the crucible, start the electric pulse treatment, and after the molten steel stage is treated for 5 minutes, perform the electric pulse treatment on the solidification stage of the molten steel; wherein the electric pulse frequency is 200 Hz, the current size is 1000 A, the voltage is 36 V, and the pulse width is 200 μm;
[0178] S5. Sample impact performance test
[0179] The steel sample in step S4 is taken out, and a 10 mm×10 mm×50 mm cuboid is obtained by electric spark wire cutting, and the impact performance is measured by an impact tester, and the impact temperature is -20°C;
[0180] S6. Detection of intracrystalline acicular ferrite in sample organization
[0181] The impact test sample in S5 was cut into 10 mm × 10 mm × 10 mm, and after being corroded with nitric acid alcohol, it was observed under a light microscope, and the area percentage of intracrystalline acicular ferrite in the sample was obtained by statistics using ImageJ software.
[0182] The results show that compared with comparative example 1, the impact energy increases from 78 J to 117 J, an increase of 50%; the area ratio of intracrystalline acicular ferrite increases from 46% to 68%, an increase of 48%.
[0183] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not depart from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for increasing the proportion of intracrystalline acicular ferrite in a structure, for use in marine engineering steel or steel for high-heat input welding, characterized in that: include: The raw materials are cleaned, heated and melted, and oxide metallurgy is added to obtain molten steel to be processed; An electrode is inserted into the molten steel to be treated and subjected to electric pulse treatment for a first time period. The molten steel to be treated is subjected to electric pulse treatment for a second time period during the solidification stage until the molten steel is completely solidified, thereby obtaining an ingot sample, wherein the first time period is different from the second time period. The pulse treatment in the first time period and the pulse treatment in the second time period are used to increase the proportion of intracrystalline acicular ferrite in the marine steel structure.
2. The method according to claim 1, characterized in that The process parameters of the electric pulse are pulse frequency of 10 Hz-10000 Hz, current of 10 A-1000 A, pulse width of 1 μs-500 ms and voltage of 1-36 V.
3. The method according to claim 2, characterized in that The method comprises the following: S1. Cut the raw material into cubic samples by wire cutting, and use sandpaper to polish, clean and dry the surface of the three-dimensional sample; S2. Selecting the electrode material, electrode size, electric pulse power supply and electric pulse wire according to the size of the three-dimensional sample; S3. The three-dimensional sample raw material is placed in an atmosphere furnace and heated to melt and oxide metallurgy is added. After a period of heat preservation, the molten steel to be treated is obtained; S4. The electrode is inserted into the molten steel to be treated, the two electrodes are placed on both sides of the crucible, and the electrode is inserted into the bottom of the crucible, and the electric pulse treatment is started. After the first time period of the molten steel stage, the electric pulse treatment is performed in the second time period during the solidification stage of the molten steel; S5. After the second time period ends, the electric pulse treatment is stopped until the molten steel is completely solidified to obtain an ingot.
4. The method according to claim 1, characterized in that: The first time period is 1 min-20 min, and the second time period is 30 min-60 min.
5. The method according to claim 3, characterized in that: The material of the electrode is high-purity iron or tungsten, the diameter of the electrode is 8-12 mm, the length is 670 mm, the wire is a nickel-plated copper wire, and the electric pulse power supply includes positive and negative electrodes.
6. The method according to claim 1, characterized in that The oxide metallurgy is one or more of Mg, Ti, Zr and rare earth elements.
7. The method according to claim 3, characterized in that The method further comprises: S6. The ingot was cut into a 10 mm × 10 mm × 50 mm cuboid, and the impact performance was measured at an impact temperature of -20 ° C to obtain an impact test sample; S7. Cut the impact test sample into a cubic sample of 10 mm × 10 mm × 10 mm, corrode the sample, and observe and count the area ratio of intracrystalline acicular ferrite in the sample.
8. The method according to claim 3, characterized in that The atmosphere of the atmosphere furnace is argon.
9. The method according to claim 3, characterized in that: The period of time is 30 minutes.
10. A marine steel or steel for high-heat-line welding, characterized in that: The marine engineering steel or steel for high-heat input welding is prepared by the method described in any one of claims 1 to 9, wherein the proportion of intracrystalline acicular ferrite in the structure is increased by 25-75%.
Citation Information
Patent Citations
Method for realizing homogenized distribution of inclusions in molten steel solidification structure
CN115921828A
Device and method for restraining inclusion in continuous casting crystallizer from growing up through pulse current
CN117862439A
Device and method for removing inclusions in molten steel through cooperation of pulse current and bubbles
CN118441122A